Deixis Analysis in the Business Article of the Jakarta Post - Herman Herman; Hilman Pardede (LPPM Universitas Bina Sarana Informatika, 2020)
This research is entitled Deixis in the Business Article of The Jakarta Post. This research is conducted in order to find out the deixis in the business article of the Jakarta Post and five articles are taken as the samples. The data is analyzed through a pragmatic theory stated by Levinson theory. The theory divides the types of deixis into 5 types, (1) person deixis (2) place deixis (3) time deixis (4) discourse deixis (5) social deixis. Problem discussed in this research: 1) what types of deixis found in the article of Jakarta Post? 2)what is the dominant type of deixis found in the article of Jakarta Post? The research method in this research used is qualitative description. The data of this research were taken from the article of the Jakarta Post. Finally, the findings show: 1) all types of deixis found in the article of the Jakarta Post, 2) the dominant types of deixis found in the article of the Jakarta Post.